"A Hard Space to Manage": The Experiences of Women of Color Faculty Teaching Online. Issue 1 (2nd January 2020) - Yao, Christina W.; Boss, Ginny Jones
Abstract : The purpose of this study is to examine the experiences of Women of Color (WOC) faculty who teach asynchronous online courses. While there is a growing body of literature on the experiences of WOC faculty and a separate body of literature on the challenges and opportunities related to online teaching, virtually no research exists on how Women of Color faculty navigate the intersections of race/ethnicity, gender, and pedagogy in an online class. Using a theoretical framework of embodiment, we investigated WOC faculty's embodiment in online teaching to better understand how (dis)embodiment impacted their teaching experiences. We explored the following research question: How do WOC faculty describe their experiences with disembodiment in asynchronous, online courses? Our analysis of the data showcases the ways in which WOC come to understand the space of online teaching, the impact of their identities in online teaching, and the utility of online teaching for engaging in critical conversation regardless of course content.